Women's social standing the empirical problem of female social class - Carr-Hill, Roy A. 1943-; Pritchard, Colin W. (Macmillan, 1992)
What is social class? Do we all have one? Such questions are usually asked about men. If women are considered at all it is usually as an appendage to one of the men in their lives. It would be astonishing if (female) social scientists did not complain. They do. The ensuing debates are fun but of no use to those who need to analyze data. This book instead focuses on the methodological issue of the appropriate form of a social classification. In Part I, the authors describe the genesis of the Registrar-General's occupationally based classification--and in particular its application to women--arguing that it is not obviously appropriate in the current context. In Part II, they set out the technical criteria which ought to be met by any index, and further argue that a social classification should have a specific domain of reference. On this basis, in Part III, they compare the discrimination provided by the occupationally based classifications with that provided by the women's own height with surprising results. The book concludes with an examination of the implications of the argument for those concerned in collecting and analyzing empirical data and for the theoretical debate about social class.
Keywords: Geschichte 1931-1980; Classes sociales - Grande-Bretagne; Classificatie; Femmes - Grande-Bretagne - Conditions sociales; Sociale stratificatie; Statut social - Grande-Bretagne; Vrouwen; Frau; Social classes -- Great Britain; Women -- Great Britain -- Social conditions; Soziale Situation; Sozialstruktur; Soziale Klasse; Beruf; Großbritannien